O discurso do novo na forma(ta)ção do sujeito-aluno: escola em tempo integral em cena - Kohler, Irene Cristina (2014)
This study has as object the discourse of the “new”, on “Novas Perspectivas para o cotidiano escolar” (2011), document for the high school in full time of Santa Catarina State. This research seeks to understand discourses about the subject-student produced by the document. Therefore, we have as hypothesis that the document when presents a new discourse on a curricular proposal, produces one imaginary about the subject-student, such as logocentric, centered, seeking perfection and completeness, according to the real historical context. We also believe that, by proposing a form of differentiated education, the document presents the discourse of the "new" as a device to produce a subject-student to work in this space. Given this hypothesis, the following questions will be taken up along our interpretive gesture, I) who is this subject-student that is through by the discourse of the "new" on the School Full-Time document? II) Who is this subject-student that the Full-Time School aims and intends to form and format? We join the discursive theory formulated by Foucault (1969 [2013], 1970 [2010], 1979 [2011], 1975 [1996]). A major contribution of this author refers to the order of discourse and archeology than identifying, as the speeches, small events, and small breaks, permit the emergence of saying camouflaged by a series of surface appearances. Affiliated to this theory we intend to: (i) analyzing regularities and dispersions about the constitution of the subjectstudent on the in school full time document, through the discourse of the "new"; (ii) reflect how the document "Novas perspectivas para o cotidiano escolar" (2011) introduced the "new" as a device for producing a subject-student molded into certain patterns and models; and (iii) reflect about the images, produced by the document in relation to the subject-student in the school full time. Thus, based on the analyzes, was observed that the document trace constituents contribute to the establishment of a regime of truth, of all that is new is to improve, even this representation of the new has already been seen at other moments on regular time. The regime of truth is ensured in educational policy discourse, which assigns truth value through the scientific status of institutionalized knowledge, which is not coming from the state, but is kept by him (Foucault, 2011). We understand that the illusion of full and complete form the subject-student, the discourse of the "new" camouflages and demarcates a boundary between what went down and proposed school full time. Thus, based on the analyzes, we could see that the discourse of the new, as a constitutive element of the text, create rules, establish as strategy and produces subjects.